A scaffolding intervention to improve self-efficacy in source-based argumentative writing - Besma Allagui (Frontiers in Psychology)
This study examined the role of scaffolding as temporary support offered by an educator to help students complete a learning task that would be challenging to accomplish without this support. Although there is a great deal of research in (L2) second language writing on the effect of scaffolding on improving students’ writing outcome variables (e.g., organization, coherence, content, and overall writing performance), few studies have explored the contributions of scaffolding to learners’ emotions and psychological variables. Using a double pre-test post-test design, this quasi-experimental study investigated the effect of a scaffolded writing intervention on students’ self-efficacy beliefs (i.e., confidence in their ability) in source-based argumentative writing. We analyzed the students’ (N = 50) source-self-efficacy beliefs 3 weeks before the intervention, immediately before the intervention, and immediately after the intervention. At the end of the intervention, students’ performance was measured using a scoring rubric containing key criteria in source-based argumentative writing. A post-study semi-structured interview was conducted with participating students (N = 13) to further understand their experience with the scaffolding intervention. The analyses demonstrated that the intervention had a positive and significant impact on students’ self-efficacy beliefs of their abilities to organize ideas, summarize different sources, and revise their essays. There were no significant changes in the participants’ beliefs about skills related to deciding if the evidence from different sources is strong, finding weaknesses in the arguments presented in different sources, and writing a counterargument. Furthermore, correlational analysis using post-test self-efficacy overall score and students’ writing performance scores on four major aspects (idea development, organization, source use, and language use) revealed a positive relationship between self-efficacy and two aspects of writing (source use and organization). Students’ interview results further confirmed the effectiveness of the intervention in enhancing the participants’ self-efficacy beliefs and performance in source-based argumentative writing. These findings highlight the importance of scaffolding strategies targeting self-efficacy to improve confidence in source-based writing and hence writing performance.